Social Commerce and Financial Performance of SMEs: A Qualitative Prospective (KASBIT Business Journal, 2025)
In the 21st century, social media has become a powerful global tool, and its popularity continues to rise. Many small and micro enterprises are increasingly turning to social media to improve their financial performance. Platforms like Facebook, blogs, Twitter, and Pinterest have become essential for these businesses, allowing them to promote and sell products while engaging with customers. This study examines how social media contributes to the growth of social commerce in small and micro enterprises in Malaysia, using the Resource-Based View (RBV) theory as a foundation. Data was collected from 100 CEOs and managers of small and micro enterprises in Malaysia through a survey, focusing on their experiences and advice for new social entrepreneurs. The results show that most of the CEOs and managers strongly recommend that small and micro enterprises take full advantage of social media. They believe it can lead to significant increases in sales and revenue. The study also highlights that, when used effectively, social media can greatly enhance the social commerce performance of small and micro enterprises, helping them achieve sustainable growth.
Keywords: Financial Performance